Thioredoxin reductase is the major selenoprotein expressed in human umbilical-vein endothelial cells and is regulated by protein kinase C. - Anema, S M (1999)
Damage to the endothelium by reactive oxygen species favours atherogenesis. Such damage can be prevented by selenium, which is thought to exert its actions through the expression of selenoproteins. The family of glutathione peroxidases (GPXs) may have antioxidant roles in the endothelium but other intracellular and extracellular selenoproteins with antioxidant actions may also be important. The selenoproteins expressed by cultured human umbilical-vein endothelial cells (HUVECs) were labelled with [(75)Se]selenite and separated using SDS/PAGE. HUVECs secreted no extracellular selenoproteins. There were distinct differences between the intracellular selenoprotein profile of (75)Se-labelled HUVECs and those of other tissues. A single selenoprotein with a molecular mass of 58 kDa accounted for approx. 43% of the intracellular (75)Se-labelled proteins in HUVECs. This protein was identified by Western blotting as the redox-active lipid-hydroperoxide-detoxifying selenoprotein, thioredoxin reductase (TR). TR expression in HUVECs was down-regulated by transiently exposing cells to the phorbol ester PMA for periods as short as 1 min. However, there was a delay of 48 h after PMA exposure before maximal down-regulation of TR was observed. The protein kinase C (PKC) inhibitor bisindolylmaleimide I hydrochloride had no effect on TR expression when added alone, but the agent prevented the down-regulation of TR expression seen with PMA. The calcium ionophore A23187 increased TR expression in HUVECs after a 12-h exposure, but the maximal effect was only observed after a 35-h exposure. These findings suggest that TR may be an important factor in the known ability of Se to protect HUVECs from peroxidative damage. Furthermore, the results also suggest that TR expression can be negatively regulated through PKC. It is possible that TR expression may be positively regulated by the calcium-signalling cascade, although TR induction by A23187 may be due to toxicity.